The impact of inflation on the level of economic activity - Odeh, H.S.; Zimmerman L.J. (Rotterdam : Rotterdam University Press, 1966)
This book described impact of inflation on the level of economic development and economic policy in Brazil and Chile.
Includes statistical appendices.
Includes bibliographical references: p. 99-101.
osa 21/09/2016
Loans
Keywords: Inflation; Chile; Brazil